STUDY ON OCCURRENCE OF LISTERIA MONOCYTOGENES IN SOIL OF PUNJAB PROVINCE AND ITS ASSOCIATED RISK FACTORS - R. Tahir1; M. Rabbani; A. Ahmad; M. Y. Tipu; M. H. Chaudhary; B. M. Jayarao (Journal of Animal and Plant Sciences, 2021)
Listeriosis, caused by Listeria monocytogenes (Lm), has zoonotic implications and has a wide host range. It has unique potential to cross blood brain barrier and placental barrier which results in encephalitis, meningitis and abortions. Initially only animals were considered as its victim but later on it emerged as an important food borne human pathogen and so far, it has been isolated from various food samples and environmental samples too. The current study is based upon the determination of genome-based distribution of L. monocytogenes (hly gene) in various soil samples collected from selected districts of Punjab province, Pakistan. The selection of the districts was based on historical information about simultaneous prevalence of the soil borne human and animal diseases... A total of 970 soil samples were processed independently by real-time PCR and an association between occurrences in soil was correlated to several categorical variables. The genome was detected in 17 samples (1.75%, 95 % CI: ±0.5), each originating from different location across districts under study. A greater number of positive soil samples for Lm genome were detected in district Attock followed by Sheikhupura, Faisalabad, Sargodha, Sahiwal and Lahore. The odds for occurrence of Lm were more at places near to water sources [2.85, CI:95% (0.9256, 8.831) p=0.05] and having more than 1000 animals per village [3.32, CI:95% (1.077, 10.27) p=0.02]. In conclusion, DNA of Lm is distributed in the soil of several districts of Punjab and fodder grown on such contaminated soil could be a potential risk factor to health of both animals and humans. Future studies are required to identify a causal relationship between presence of bacterium in soil to seroconversion in animal and human and prevalent serotypes across a wide geographical range across Pakistan.
Keywords: Listeriamonocytogenes; Real time PCR hly gene; soil